2016
DOI: 10.1016/j.prevetmed.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Broken biosecurity? Veterinarians’ framing of biosecurity on dairy farms in England

Abstract: 11There is seen to be a need for better biosecurity -the control of disease spread on and off

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 62 publications
2
61
0
1
Order By: Relevance
“…It is apparent that some dairy cattle farmers may be making judgements about whether preventive practices are worth undertaking based on their own individual risk assessment which is likely to be informed by previous experience and tacit knowledge, which has been reported in a recent study [33]. It has been shown that risk can mean different things to different people, with experts and lay people contrasting in their perception of risk of the same activity [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is apparent that some dairy cattle farmers may be making judgements about whether preventive practices are worth undertaking based on their own individual risk assessment which is likely to be informed by previous experience and tacit knowledge, which has been reported in a recent study [33]. It has been shown that risk can mean different things to different people, with experts and lay people contrasting in their perception of risk of the same activity [47].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most frequently applied models used within the health psychology field is the Theory of Planned Behaviour [33]. The Theory of Planned Behaviour (TPB) aims to determine the association between attitudes, beliefs, intentions and the perceived behavioural control an individual feels they have over a particular behaviour, as well as how these perceptions predict actual behaviour; Figure 1 [20,33].…”
Section: Introductionmentioning
confidence: 99%
“…Vets express frustration that they cannot interact with farmers enough to improve biosecurity, farmers do not take their advice, and biosecurity should be a greater priority for the dairy sector (Shortall et al . ). Vets can have different roles within government, industry and private practice (Escobar and Demeritt ); this article focuses on the vet‐farmer relationship within private practice.…”
Section: Introductionmentioning
confidence: 97%
“…), recent research has identified the importance of the cultural meanings farmers bring to biosecurity practices (Shortall et al . ). Despite research suggesting low levels of uptake of biosecurity measures (Brennan and Christley ), previous social science research has shown that taking care of animals’ health and welfare is seen as a key part of good farming identity (Gray ; Burton ; Wilkie ; Haggerty et al .…”
Section: Introductionmentioning
confidence: 97%
“…Training was recommended to be provided by veterinary surgeons and face-to-face was the preferred format. Moreover, training should be tailor-made to cover the audience needs as highlighted in a recent UK study on veterinary practitioners specialised in dairy cattle [14]. Therefore the veterinary profession needs to be more involved in on farm biosecurity training.…”
Section: Discussionmentioning
confidence: 99%